2008
DOI: 10.1002/jcb.21674
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the calcitonin receptor, calcitonin receptor‐like receptor, and receptor activity modifying proteins during osteoclast differentiation

Abstract: The expressions of the calcitonin receptor (CTR), the calcitonin receptor-like receptor (CLR), the receptor activity-modifying proteins (RAMP) 1-3, and of the receptor component protein (RCP) have been studied in mouse bone marrow macrophages (BMM) during osteoclast differentiation, induced by treatment with M-CSF and RANKL. Analyses of mRNA showed that CLR and RAMP1-3, but not CTR, were expressed in M-CSF stimulated BMM. RANKL gradually increased CTR mRNA, transiently enhanced CLR and transiently decreased RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 30 publications
(41 reference statements)
3
36
1
1
Order By: Relevance
“…The functional receptor for CGRP is a complex form of RAMP1 and calcitonin receptor-like receptor (Naot and Cornish 2008). Previous studies have demonstrated that these proteins are expressed by osteoblasts in the human as well as bone marrow cells in the human and mouse (Uzan et al 2004;Granholm et al 2008). Osteoclast-like cells from co-cultures of mouse bone marrow cells and spleen cells are devoid of RAMP1 (Granholm et al 2008).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The functional receptor for CGRP is a complex form of RAMP1 and calcitonin receptor-like receptor (Naot and Cornish 2008). Previous studies have demonstrated that these proteins are expressed by osteoblasts in the human as well as bone marrow cells in the human and mouse (Uzan et al 2004;Granholm et al 2008). Osteoclast-like cells from co-cultures of mouse bone marrow cells and spleen cells are devoid of RAMP1 (Granholm et al 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have demonstrated that these proteins are expressed by osteoblasts in the human as well as bone marrow cells in the human and mouse (Uzan et al 2004;Granholm et al 2008). Osteoclast-like cells from co-cultures of mouse bone marrow cells and spleen cells are devoid of RAMP1 (Granholm et al 2008). However, CGRP is known to have effects on rat osteoclasts (Naot and Cornish 2008;Wang et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…16,17 The human RAMP-1 gene is located on chromosome 2, at 2p36-2q37.1, spanning approximately 60 kb and containing 3 exons. RAMP1 protein has 148 amino acids with a 26-amino-acid N-terminal signal peptide, an extracellular domain of approximately 90 amino acids, a single transmembrane domain of 20 amino acids and a C-terminal tail of 10 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The indirect inhibitory effect of CGRP on osteoclastogenesis was demonstrated by regulating the Rankl/OPG ratio in osteoblast-like cells. Besides osteoblasts, osteoclasts and their precursors, bone marrow-derived macrophages (BMM), also express the CGRP receptor complex of CRLR and RAMP1 [106]. In addition, RAMP2 and 3 mRNA and protein expression was detected in osteoclasts, which points to regulatory control from other proteins of the calcitonin family apart from CGRP, i.e., amylin, adrenomedullin and intermedin.…”
Section: Sensory and Sympathetic Neurotransmitters And Their Recepmentioning
confidence: 99%